Bond−Energy−Electron Relaxation of BeN Nanoclusters and BeX Alloys. Issue 8 (20th June 2018) - Zhou, Junquan; Bo, Maolin; Li, Lei; Huang, Zhongkai; Tian, Meizi; Yao, Chuang; Peng, Cheng
Abstract: By combining bond order‐length‐strength (BOLS) notion and density functional theory (DFT) calculations, the bond−energy−electron relaxtion of Be N nanoclusters and BeX (C, S, B, Cl, Cu, Co, Te) alloys are studied. The results show that the size and shape of the Be nanoclusters will cause the binding energy (BE) shift, the local densification of electrons and quantum entrapment. Actions exemplified the atomic coordination ratio and the BE of BeX alloys can predict the quantitative information regarding the change of the bond length, local bond strain, bond energy density and atomic cohesive energy. Abstract : The BOLS‐DFT method is a powerful tool for detecting electrons of Be N clusters and BeX alloys in the valence band and below, showing the local chemical bond and coordination environment and its effect on the electron energy and structure of deeper core band.